2009
DOI: 10.1007/s00787-008-0713-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a French version of the junior temperament and character inventory

Abstract: The junior temperament and character inventory (JTCI) has been developed for the assessment of temperament and character dimensions in childhood based on Cloninger's model of personality. We evaluated the psychometric proprieties of a French child and parent-rated version of the JTCI based on a previous German version, and assessed the correlations between the JTCI dimension scores and the scores on the child behavior checklist (CBCL) in a community sample of French children and adolescents aged 10-16 years. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 41 publications
(50 reference statements)
3
12
0
Order By: Relevance
“…Although in line with previous research, both in the US and internationally (e.g. Cloninger et al, 1993;Kijima et al 1996;Isen, Baker, Raine, & Bezdjian, 2009;Asch et al, 2009;Garcia, Aluja, Garcia, Escorial, & Blanch, 2012), this finding casts doubt on the reliability of the measurements. One explanation could be the low number of items in specific scales, since alpha increases with number of items (John & Soto, 2007).…”
Section: Strengths and Limitationssupporting
confidence: 84%
“…Although in line with previous research, both in the US and internationally (e.g. Cloninger et al, 1993;Kijima et al 1996;Isen, Baker, Raine, & Bezdjian, 2009;Asch et al, 2009;Garcia, Aluja, Garcia, Escorial, & Blanch, 2012), this finding casts doubt on the reliability of the measurements. One explanation could be the low number of items in specific scales, since alpha increases with number of items (John & Soto, 2007).…”
Section: Strengths and Limitationssupporting
confidence: 84%
“…It evaluates four temperaments (individual differences in the response to stimuli, identifiable early in development and moderately heritable)-novelty seeking, harm avoidance, reward dependence, and persistence-and three characters (influenced by social learning and maturing throughout the life span)-self-directness, cooperativeness, and self-transcendence. A previous validation study of this questionnaire in two secondary school samples in France showed internal consistency values greater than 0.70 for all dimensions (except for self-transcendence and reward dependence, for which the internal consistency was 0.56 and 0.58, respectively; Asch et al, 2009). …”
Section: Methodsmentioning
confidence: 80%
“…With an estimated worldwide prevalence of around 5% [2], ADHD is one of the most commonly diagnosed neurodevelopmental disorders. ADHD is frequently comorbid with other conditions such as oppositional defiant disorder, conduct disorder, specific learning disorders, mood and anxiety disorders, substance use disorders, sleep disturbances and other neurodevelopmental disorders such as autism spectrum disorder [3][4][5][6][7][8], as well as with somatic conditions such as obesity [6,9,10].…”
Section: Introductionmentioning
confidence: 99%